A review on additive manufacturing of ceramic materials based on extrusion processes of clay pastes - Ruscitti, Andrés Federico (2020)
This paper aims to present a state of the art of additive manufacturing (AM) of ceramic materials based on extrusion processes of clay pastes, reviewing the definitions and classifications of the AM field under current international standards. A general overview on the AM category ‘material extrusion’ is provided and the class ‘paste deposition modeling’ is proposed for those techniques based on the extrusion of pastes that are solidified by solvent vaporization, with the aim of distinguishing it from the class ‘fused deposition modeling’, which is applied to extruded polymers through temperature plasticization. Based on the survey of background information on 3D printing technology by ceramic paste extrusion, a classification and historization of the innovations in the development of this technology are proposed.